Prevalence of Recurrent Bell’s Palsy : Prevalence of Recurrent Bell’s Palsy - Atif, Malik Muhammad; Hussain, Kazim; Naeem, Iqra; Asghar, Zulkaif; Batool, Fariha; Butt, Saba; Khalil, Aisha (Pakistan Journal of Health Sciences, 2024)
Recurrent Bell’s palsy is experiencing more than 1 episode of Bell’s palsy after recovering from the first one. Prevalence of Recurrent Bell’s Palsy ranges from 2.6-15.2% although it is a rare occurrence. The study under observation was conducted to find out the prevalence of Recurrent Bell’s Palsy in patients. Objective: To assess the prevalence of recurrent Bell’s palsy. Methods: A convenience sampling method was used to perform an observational cross-sectional analytical survey based on inclusion and exclusion criteria. Data were collected by using questionnaire after informed consent and was analyzed using SPSS version 26.0. Results: It was concluded that mean age of Recurrent Bell’s palsy patients was 40.8 years. Male and female both genders were involved. Most common Bell’s palsy-related predisposing factors were hypertension, Diabetes, old age, and Pregnancy respectively. More cases were reported in winter season than summers in recurrent Bell’s palsy patients. Conclusions: The prevalence of RBP is 4.2% and most commonly associated risk factors are Hypertension, Diabetes, Positive family history and pregnancy.